1995
DOI: 10.1007/bf02245194
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous morphine self-administration by rats with low versus high saccharin preferences

Abstract: An experiment was performed to determine the relationship between saccharin preference and the self-administration of morphine via the oral and intravenous routes. On the basis of voluntary intake of a saccharin solution by male rats, low and high preference groups were formed. Rats selected for high saccharin preference self-administered more morphine intravenously than rats selected for low preference. The two groups did not differ in oral morphine intake. The positive relationship between the intake of sacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 23 publications
3
24
1
Order By: Relevance
“…This phenomenon parallels the enhancement, by food restriction, of drug self-administration (Carroll and Meisch 1984) and conditioned place preference (Bell et al 1997), and appears to reflect an increase in sensitivity of the neural substrate for drug reward (Cabeza de Vaca and Carr 1998). The augmentation of drug reward by food restriction is just one of numerous observations that support an association between drug-seeking and ingestive behavior (Sills et al 1998;Gosnell et al 1995;Comer et al 1996;Sills and Vaccarino 1994;Gosnell 2000). Although the physiological mechanisms underlying the augmentation of drug reward by food restriction have not been established, the augmented rewarding effect of amphetamine in food-restricted subjects is associated with increased cfos expression in limbic forebrain dopamine terminal areas (Carr and Kutchukhidze 2000).…”
Section: Introductioncontrasting
confidence: 39%
“…This phenomenon parallels the enhancement, by food restriction, of drug self-administration (Carroll and Meisch 1984) and conditioned place preference (Bell et al 1997), and appears to reflect an increase in sensitivity of the neural substrate for drug reward (Cabeza de Vaca and Carr 1998). The augmentation of drug reward by food restriction is just one of numerous observations that support an association between drug-seeking and ingestive behavior (Sills et al 1998;Gosnell et al 1995;Comer et al 1996;Sills and Vaccarino 1994;Gosnell 2000). Although the physiological mechanisms underlying the augmentation of drug reward by food restriction have not been established, the augmented rewarding effect of amphetamine in food-restricted subjects is associated with increased cfos expression in limbic forebrain dopamine terminal areas (Carr and Kutchukhidze 2000).…”
Section: Introductioncontrasting
confidence: 39%
“…[33][34][35] Furthermore, the rats either selected or bred for high or low sweet intake show corresponding differences in the acquisition or amount of self-administered amphetamine, cocaine, and morphine. [36][37][38][39] In humans, opiate-dependent subjects on methadone maintenance report higher consumption of sweets than control subjects, 40 and subjects diagnosed with alcohol dependence or cocaine abuse/dependence tend to prefer sweeter sucrose solutions than controls. 41,42 After reviewing the similarities between the effects of sugar ingestion and those related to drug addiction, Avena et al 43 conclude that under some circumstances, sugar can be addictive.…”
Section: Interactions Between Palatability and Drugs Of Abusementioning
confidence: 43%
“…In addition, rats selectively bred for high or low ethanol intake show parallel differences in saccharin intake (Sinclair et al 1992). Gosnell et al (1995) reported that rats with a high preference for saccharin self-administered more morphine than rats with a low preference. In human subjects, the peak of the sucrose concentration-preference curve was at a higher concentration for abstinent alcoholics than for controls (Kampov-Polevoy et al 1997).…”
Section: Introductionmentioning
confidence: 48%